Perbandingan Pemilihan Antara Tipe Wellhead Conventional Dengan Wellhead Unihead - Nugroho Marsiyanto; Aly Rasyid; Sigit Widianto (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
The wellhead is a surface well control device made of steel which forms a seal / baffle system to withstand bursts or leaks of liquid from the well to the surface composed of casing head (casing hanger) and tubing head (tubing hanger). Wellhead used in an oil or gas well must have a long runlife because an oil or gas well can last up to decades, and if it is necessary to replace the wellhead will take large costs. This paper determines the process in selecting the use and effectiveness of wellhead and comparing conventional wellhead versus unihead wellhead at W well that is efficient and safe during drilling well and optimal utilization during production process. Wellhead type selection process cover determining temperature class, material class, pressure rating, installation costs, and in terms of safety. Based on the selection process, W wellhead well has the temperature class used is class U, the material class used is the type FF- 0.5 or HH-0.5, for a pressure rating of 3000 psi, and in terms of cost it is more economical to use unihead wellhead type.